An investigation of metal transfer process in GMAW - WĘGLOWSKI, M. S.; HUANG, Y.; ZHANG, Y. M. (Engineering Transactions, 2014)
This paper presents the studies of the metal transfer process in gas metal arc welding with mild steel electrode. It aims at mathematic description of the droplet flight trajectory, droplet velocity and acceleration. To this end, the droplet flight trajectory was first fitted using the 3rd order polynomial regression and it was found that the model can be reduced to the 2nd order. The average diameter of a droplet, transfer rate of droplets, average velocity and acceleration of a droplet were calculated. The geometric shape factor was estimated. A new metal transfer monitoring method which is based on narrow band filter and does not require He-Ne laser, has been used in this study to observe the metal transfer process.